Pola Asuh Anak Dalam Keluarga di Lingkungan Lokalisasi Padang Bulan Banyuwangi - Ristanti, Kurnia; Hidayat, Nurul (University of Jember, 2016)
Abstract Family and community are determining factors of children personality. In family, children are introduced to a wide range of values and norms. The family is the first place of socialization for children, and then the second socialization is the community. If the children should ideally live in conducive neighborhood to support their growth, the case of children who live in prostitution environment is in opposition. Many children in the school who still live in are cared in prostitution environment “Padang Bulan” Banyuwangi. They grow up in an environment whose surroundings are focused on pornography. Their parents’ profession as pimps and their house in the prostitution environment make the children live in the prostitution environment. This research aimed to determine, describe and analyze the patterns of child care applied by parents to their children. The research used qualitative approach, and the informants were selected by purposive sampling involving pimps as the research subjects who had children and lived in the prostitution. There were three kinds of values instilled by parents to their children: value of morality, religious value and value of virtue in selecting friendship neighborhood.